Activating PKC-ε induces HIV expression with improved tolerability. - Alivelu M Irrinki; Jasmine Kaur; Bally Randhawa; Ryan McFadden; Chelsea Snyder; Hoa Truong; Daniel Soohoo; Eric Hu; Helen Yu; Bernard P Murray; Bing Lu; Dmytro Kornyeyev; et al. (PLoS Pathogens)
Despite suppressive antiretroviral therapy (ART), HIV-1 persists in latent reservoirs that seed new HIV infections if ART is interrupted, necessitating lifelong therapy for people with HIV. Activation of latent HIV during ART could improve recognition and elimination of infected cells by the immune system. Protein kinase C (PKC) isozymes increase HIV transcription and hence are potential latency reversal agents. However, the clinical utility of PKCs for this application is limited due to toxicity, which is poorly understood. Our studies showed that PKC activation with multiple classes of agonists leads to widespread platelet activation, consistent with disseminated intravascular coagulation, at concentrations that were similar to those required for T-cell activation. Differential expression analysis indicated that PKC-ε and PKC-η isoforms are expressed at high levels in human CD4+ T cells but not in platelets. Using structure-based drug design, we developed a novel PKC agonist, C-233, with increased selectivity for PKC-ε. C-233 increased both supernatant HIV RNA and p24 expression ex vivo after treatment of CD4+ T cells from ART-suppressed people with HIV. C-233 was 5-fold more potent for T-cell activation relative to platelet activation. Our studies support the use of structure-based drug design to create selective novel PKC agonists for the safe activation of HIV reservoirs and improved tolerability.